2007
DOI: 10.26530/oapen_459398
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic Explorations (TA26) : Lapita and Western Pacific Settlement

Abstract: terra australis 26Terra Australis reports the results of archaeological and related research within the south and east of Asia, though mainly Australia, New Guinea and island Melanesia -lands that remained terra australis incognita to generations of prehistorians. Its subject is the settlement of the diverse environments in this isolated quarter of the globe by peoples who have maintained their discrete and traditional ways of life into the recent recorded or remembered past and at times into the observable pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Such is the case with Lapita pottery, associated with the first human presence in Remote Oceania about 3000 years ago. Given the widespread sharing of intricate decorative motifs, highly organised designs and remarkable vessel forms across Vanuatu, New Caledonia, Fiji, Samoa and Tonga, archaeologists generally believe that the people who manufactured and used decorated Lapita pots attributed great cultural significance to their iconography (Chiu 2007;Mead 1975;Sand and Bedford 2010;Siorat 1990). Current models assume that the symbolic significance of these vessels was more important than their economic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such is the case with Lapita pottery, associated with the first human presence in Remote Oceania about 3000 years ago. Given the widespread sharing of intricate decorative motifs, highly organised designs and remarkable vessel forms across Vanuatu, New Caledonia, Fiji, Samoa and Tonga, archaeologists generally believe that the people who manufactured and used decorated Lapita pots attributed great cultural significance to their iconography (Chiu 2007;Mead 1975;Sand and Bedford 2010;Siorat 1990). Current models assume that the symbolic significance of these vessels was more important than their economic value.…”
Section: Discussionmentioning
confidence: 99%
“…Current models assume that the symbolic significance of these vessels was more important than their economic value. It has been suggested that dentate-stamped Lapita ceramics were used to promote, signal and convey information about the social status and power of Lapita communities, notably in the contexts of special events and/or ceremonies, such as funerals or feasts for example (Best 2002;Chiu 2007;Spriggs 2003;Terrell and Welsch 1997). The archaeological record shows that generally Lapita occupations have been relatively short-lived (200 years maximum) and quickly followed by the emergence of distinctive regional decorative styles, perhaps signalling the decreased significance of Lapita pottery following the disintegration of a shared cultural system.…”
Section: Discussionmentioning
confidence: 99%